Prediksi Financial Distress dengan Model Zmijewski dan Grover pada Perusahaan Retail yang Terdaftar di BEI Selama Tahun 2015 - 2019 - Wiwin Wiranti; Aris Munandar (Program Studi Manajemen Fakultas Ekonomi UMRAH, 2021)
The sales growth of retail companies has faced a shrinking trend over the past 5 years. Many companies face financial difficulties because of the incident. There are several companies that in achieving the target of making a profit experience losses and have the potential to go bankrupt. This study aims to predict financial distress using the zmijewski and grover testing model in retail companies listed on the IDX. This study uses analysis with the Zmijewski model and the Grover model, using descriptive statistical analysis and hypothesis testing with the one-sample t-test. Based on the results of the analysis with the zmijewski model and grover retail companies listed on the IDX do not experience financial distress, descriptive statistical analysis shows that the model with the highest level of accuracy is the zmijewski model of 1.43, hypothesis testing with a sample t-test one sample of retail companies has no financial potential distress.